PLURALISM AND MULTICULTURALIZM EDUCATION - Iwan Ridwan Paturochman; Supian Ramli; Iwan Ridwan; Fauziah Nasution; Opan Arifudin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Education pluralism and multiculturalism have become an important focus in contemporary education discussions. In an era of increasingly interconnected globalization, pluralism and multiculturalism have become crucial in building societies that are inclusive, tolerant, and accepting differences. The main objective of this journal is to explore the importance of education pluralism and multiculturalism in shaping awareness and acceptance of differences in an educational context. The research uses a qualitative approach involving a literary review and conceptual analysis. Education of pluralism and multiculturalism is essential in building inclusive societies. Through the understanding and awareness developed through this education, students can appreciate cultural, ethnic, religious, and social background differences. This approach also helps develop students' social and intercultural skills. Challenges in its implementation include inadequate curricula, lack of teacher training, and resistance to change. Government support, educational institutions, and the public are needed to ensure the success of education pluralism and multiculturalism. In conclusion, education plays an important role in shaping inclusive societies, but further efforts are needed to address implementation challenges and integrate them into existing education systems.